Hospitalization in fibromyalgia: a cohort-level observational study of in-patient procedures, costs and geographical variation in England - Soni, A; Segerdahl, A; Javaid, M; Pinedo-Villanueva, R; Tracey, I (Oxford University Press, 2019)
Objectives Fibromyalgia is a complex, debilitating, multifactorial condition that can be difficult to manage. Recommended treatments are usually delivered in outpatient settings; evidence suggests that significant inpatient care occurs. We describe the scale and cost of inpatient care with a primary diagnostic code of fibromyalgia within the English National Health Service. Methods We conducted a cohort-level observational study of all patients admitted to hospital due to a diagnosis of fibromyalgia, between 1 April 2014 and 31 March 2018 inclusive, in the National Health Service in England. We used data from Hospital Episode Statistics Admitted Patient Care to study: the age and sex of patients admitted, number and costs of admissions, length of stay, procedures undertaken, class and type of admission, and distribution of admissions across clinical commissioning groups. Results A total of 24 295 inpatient admissions, costing £20 220 576, occurred during the 4-year study period. Most patients were women (89%) with peak age of admission of between 45 and 55 years. Most admissions were elective (92%). A number of invasive therapeutic procedures took place, including a continuous i.v. infusion (35%). There was marked geographical variation in the prevalence and cost of inpatient fibromyalgia care delivered across the country, even after accounting for clinical commissioning group size. Conclusions Many patients are admitted for treatment of their fibromyalgia and given invasive procedures for which there is weak evidence, with significant variation in practice and cost across the country. This highlights the need to identify areas of resource use that can be rationalized and diverted to provide more effective, evidence-based treatment.